Formação continuada em pensamento computacional para professores do ensino fundamental: computação desplugada nas práticas educativas - Bulcão, Jeanne da Silva Barbosa (2021)
In line with world trends, Brazil recently approved the National Common Curricular Base (BNCC) and included 10 general competencies that students must achieve by the last stage of Basic Education. These general competencies are related to those identified in the international scenario as necessary for the formation of citizens and professionals in the 21st century. Among these skills, those related to Computational Thinking stand out, which involve pattern recognition, abstraction, logical reasoning, creative thinking, all culminating in the ability to solve problems, which is considered one of the most important skills in the current social and professional life. As a result, the training of students, in today's social, cultural, professional and technological scenario, requires teachers to have new skills and professional competences that were not given to them during their initial training. Therefore, for teachers to stimulate Computational Thinking with students, it is necessary to train them for a change of mentality about pedagogical possibilities in the face of conditions of technological scarcity in their work environment, as well as for knowledge about what is and how to apply it in teaching and learning processes. It is in this context that this work aims to contribute by presenting a model of continuing education in Computational Thinking capable of stimulating the development of skills related to the subject in teachers, motivating them to take this knowledge to their students through practices of Unplugged Computing in schools. . The work systematized a first version of the continuing education course in Computational Thinking for teachers, which took place in 2019, in face-to-face format, within the scope of the Norte-rio-grandense Program of Computational Thinking, which served as a pre-test to evaluate the strategies, methodologies and resources applied in order to propose improvements for the construction of a new training model. The new version of the course was taught in 2020 following the model proposed in this work, adapting to the online format due to the reality imposed by the Covid-19 pandemic. The results obtained indicate that some teachers understood the concept of Computational Thinking, learned how to integrate the PC in their teaching practices and developed the technological pedagogical knowledge of the content. In addition, comparing the two editions of the course, it was possible to verify that the presential offer helped in the execution of practical and collaborative activities, but had a negative impact on the teachers' routine due to the need to travel to the training unit. On the other hand, the online offer ensured greater adhesion and participation of teachers, but made it difficult to apply the evaluation in pairs. It is concluded, therefore, that training with a practical bias, which focuses on the acquisition of skills and competences, allows the development of the expected potential to build a teaching identity that matches the contemporary needs of the profession, stimulating the ability to solve problems and the development of technological pedagogical knowledge about Computational Thinking, which includes the curation and creation of materials related to the theme, as well as the application of educational practices in schools in the teaching network.